Stable double-heavy tetraquarks: Spectrum and structure - Q. Meng (Physics Letters B, 2021)
Bound states of double-heavy tetraquarks are studied in a constituent quark model. Two bound states are found for isospin and spin-parity I(JP)=0(1+) in the bbu¯d¯ channel. One is deeply bound and compact made of colored diquarks, while the other is shallow and extended as a BB⁎ molecule. The former agrees well with lattice QCD results. A systematic decrease in the binding energy is seen by replacing one of the heavy quarks to a lighter one. Altogether we find ten bound states. It is shown for the first time that hadrons with totally different natures emerge from a single Hamiltonian.